2013
DOI: 10.1021/la304696y
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Graphite Oxide with Magnetic Chitosan for the Preparation of a Nanocomposite Dye Adsorbent

Abstract: In the current study, the functionalization of graphite oxide (GO) with magnetic chitosan (Chm) was investigated to prepare a nanocomposite material (GO-Chm) for the adsorption of a reactive dye (Reactive Black 5). The synthesis mechanism was investigated by various techniques (SEM/EDAX, FTIR spectroscopy, XRD, XPS, DTA, DTG, VSM). Characterization results indicated that a significant fraction of the amines of the chitosan (i) were inserted between the GO layers and (ii) reacted with carboxyl and epoxy groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
179
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 346 publications
(195 citation statements)
references
References 53 publications
9
179
0
Order By: Relevance
“…The strong band at 1045 cm -1 is due to the C-O bond, and the 998 cm -1 band is attributed to the stretching vibrations of C-H groups. FTIR spectrum reported in this study is in accord with previous data graphite oxide [18,19] and for grapheme oxide [22][23][24].…”
Section: Characterization Of Graphene Oxidesupporting
confidence: 91%
See 3 more Smart Citations
“…The strong band at 1045 cm -1 is due to the C-O bond, and the 998 cm -1 band is attributed to the stretching vibrations of C-H groups. FTIR spectrum reported in this study is in accord with previous data graphite oxide [18,19] and for grapheme oxide [22][23][24].…”
Section: Characterization Of Graphene Oxidesupporting
confidence: 91%
“…The adsorption experiments performed demonstrated the high capacity of GO as an adsorbent of AO [19,28]. UV-visible spectra performed in solutions of acridine orange showed the characteristic absorption peaks at wavelengths among 440 to 510 nm.…”
Section: Adsorption Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The GO/f-CS/polyamide (PA) composite membranes showed superior performance compared to the unmodified PA membrane in terms of hydrophilicity, surface smoothness, water flux, and antifouling. Travlou et al [53] researched magnetic GO-CS, and thermomechanical analysis suggested that this material has a high adsorption capacity for sewage.…”
Section: Applications In Sewage Treatmentmentioning
confidence: 99%